2009
DOI: 10.1097/ta.0b013e31818080e9
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Placement of Iliosacral Screws Without Electrodiagnostic Monitoring

Abstract: Using a standardized technique, appropriate and reliable fluoroscopic landmarks are available in the vast majority of percutaneous iliosacral screw fixation procedures. Iliosacral screw placement without neurodiagnostic monitoring has a low rate of neurologic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Ten millimeters was chosen to provide 1 to 2 mm of circumference around a 6.3 to 8-mm-diameter screw, and has been previously established as a reasonably ''safe''-diameter corridor by experienced surgeons 4,29,37 . The smallest cross-sectional area that we measured in a first sacral osseous corridor was 206 mm 2 . In comparison, an 8-mm iliosacral screw has a cross-sectional area of 50.2 mm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten millimeters was chosen to provide 1 to 2 mm of circumference around a 6.3 to 8-mm-diameter screw, and has been previously established as a reasonably ''safe''-diameter corridor by experienced surgeons 4,29,37 . The smallest cross-sectional area that we measured in a first sacral osseous corridor was 206 mm 2 . In comparison, an 8-mm iliosacral screw has a cross-sectional area of 50.2 mm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that patients with all of these characteristics have a more narrow and angled osseous corridor in the first sacral segment compared with those who exhibit none of these characteristics 23,28,29 . Using these criteria to adjust operative planning, surgeons can achieve percutaneous fixation of pelvic fractures with low rates of neurovascular injury, ranging from 0% to 1% 2,6 . We studied a large cohort of uninjured pelves to represent the variance in morphology within the general population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many fixation methods are currently used to treat posterior pelvic ring injuries clinically (Sagi et al, 2004;Schildhauer et al, 2002Schildhauer et al, , 2003Yinger et al, 2003;Ziran et al, 2003;Vanderschot et al, 2001;Kobbe et al, 2012), and the iliosacral screw (ISS) technique (Ponsen et al, 2006) has been widely used (Cole et al, 1996;Shuler et al, 1995;Sciulli et al, 2007;Gardner & Chip Routt, 2010;Gardner et al, 2009;Zwingmann et al, 2010;Kim et al, 2012;Oh et al, 2008) because of its reliable fixation strength, small wound, decreased bleeding, and low infection rate. Mears & Velyvis (2003) described the pelvis as a "three-column structure."…”
Section: Discussionmentioning
confidence: 99%